DIFFERENCES BETWEEN ENGLISH AND UZBEK GRAMMAR - Avgonova Dinora Abdumurod qizi; Urolova Rayxona Jamshid qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   This  article  explores  the  key  grammatical  differences  between  English  and Uzbek languages. Due to their belonging to different language families—Germanic and Turkic—their morphosyntactic structures differ significantly. The study focuses on  distinctions  in  sentence  structure,  tense  systems,  and  grammatical  expression. Special attention is given to translation challenges arising from these differences. The findings  highlight  the  importance  of  understanding  both  languages’  grammatical features to ensure accurate and natural communication.